Magistério extrativista da terra do meio - experiências de currículo como território educativo na floresta amazônica - LOPES, Raquel da Silva (Universidade Federal da Paraíba, 2022)
This paper introduces a curricular experience as an everyday exercising of the idea of educational territory. As this work acknowledges the risks entailed in the semantic-conceptual plurality of that category, it also seeks nevertheless to aggregate within its reach a series of educational experiences deriving from the project Gatherer Communities Teachers’ Education, inside the Amazon forest, in a region known as Terra do Meio (Middle Land), at the confluence of the rivers Xingu and Iriri, which incontestably evince the concrete possibility for the subversion of a pre-established “curricular order” as condition for the operationalization of the pedagogical work, whose main and most perverse consequence is the displacing of the reality of the territory in which such work occurs, culminating in an almost absolute artificialization of the whole experience of school education carried out with traditional peoples and communities. Therefore, inspired by the approach by the cartography method, this paper intends to indicate pieces of evidence regarding school counterculture, which becomes possible due to a conception of the curriculum as practice both rooted in life experience and intertwined in the fabric of the territory where it takes place. The territory is, beyond the space where things happen, an educational factor with a high pedagogical potential for all individuals involved in the experience. Accordingly, this article assumes the educational experience rooted in the territory as the right to a full development of the human vocation, to a becoming, but a viable becoming, which is in consonance with the necessities of concrete individuals, historically situated and existentially potent.